Starmaya: The First Arabica F1 Coffee Hybrid Produced Using Genetic Male Sterility - Georget, Frédéric; Marie, Lison; Alpizar, Edgardo; Courtel, Philippe; Bordeaux, Mélanie; Hidalgo, Jose Martin; Marraccini, Pierre; Breitler, Jean-christophe; Déchamp, Eveline; Poncon, Clément; Etienne, Hervé; Bertrand, Benoit (Frontiers in Plant Science, 2019)
In the present paper, we evaluated the implementation of a seed production system based on the exploitation of male sterility on coffee. We studied specifically the combination between CIR-SM01 and Marsellesa® (a Sarchimor line), which provides a hybrid population called Starmaya. We demonstrated that the establishment of seed garden under natural pollination is possible and produces a sufficient amount of hybrid seeds to be multiplied efficiently and economically. As expected for F1 hybrid, the performances of Starmaya are highly superior to conventional cultivars. However, we observed some heterogeneity on Starmaya cultivar in the field. We confirmed by genetic marker analysis that the off-types were partly related to the heterozygosity of the CIR-SM01 clone and could not be modified. Regarding the level of rust resistance of Starmaya cv., we saw that it could be improved if Marsellesa was more fully fixed genetically. If so, we should be able to decrease significantly the percentage of rust incidence of Starmaya from 15 to 5%, which would be quite acceptable at a commercial level. Starmaya represents the proof of concept for the mass propagation of Arabica F1 hybrid seeds using male sterility. Finally, we discuss the possibility to increase the number of hybrid varieties produced by seed, exploring some initiatives to identify male sterility markers to induce male sterility on any conventional cultivar. This would definitively open up the universe of known Arabica cultivars to be used in breeding new F1 hybrids.